2015
DOI: 10.1002/2015gl064485
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial OH nightglow measurements during the Rosetta flyby

Abstract: We present a study of the terrestrial hydroxyl nightglow emissions observed with the Visible and Infrared Thermal Imaging Spectrometer on board the Rosetta mission. During these observations, the OH Δv = 1 and 2 sequences were measured simultaneously. This allowed investigating the relative population of the v = 1 to 9 vibrational levels by using both sequences. In particular, the relative population of the vibrational level v = 1 is determined for the first time from observations. The vibrational population d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 48 publications
(72 reference statements)
6
20
0
Order By: Relevance
“…Similarly, Hässig et al (2015) observed heterogeneities in the coma of 67P with large fluctuations in composition from ROSINA data from August and September 2014. This was confirmed by the VIRTIS-H measurements of 67P from November 2014 to January 2015 (Bockelée-Morvan et al 2015) and the VIRTIS-M mapping of very inner coma of 67P during mid-April 2015 (Migliorini et al 2016). Indeed, the VIRTIS-M observations followed the evolution of the coma of comet 67P with an unprecedented spatial resolution of about 40 m/pixel, showing that H 2 O is mostly emanating from the neck connecting the two principal lobes, while CO 2 emanates mostly from both the so-called head and southern latitude regions of the large lobe (Migliorini et al 2016).…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…Similarly, Hässig et al (2015) observed heterogeneities in the coma of 67P with large fluctuations in composition from ROSINA data from August and September 2014. This was confirmed by the VIRTIS-H measurements of 67P from November 2014 to January 2015 (Bockelée-Morvan et al 2015) and the VIRTIS-M mapping of very inner coma of 67P during mid-April 2015 (Migliorini et al 2016). Indeed, the VIRTIS-M observations followed the evolution of the coma of comet 67P with an unprecedented spatial resolution of about 40 m/pixel, showing that H 2 O is mostly emanating from the neck connecting the two principal lobes, while CO 2 emanates mostly from both the so-called head and southern latitude regions of the large lobe (Migliorini et al 2016).…”
Section: Introductionsupporting
confidence: 56%
“…This was confirmed by the VIRTIS-H measurements of 67P from November 2014 to January 2015 (Bockelée-Morvan et al 2015) and the VIRTIS-M mapping of very inner coma of 67P during mid-April 2015 (Migliorini et al 2016). Indeed, the VIRTIS-M observations followed the evolution of the coma of comet 67P with an unprecedented spatial resolution of about 40 m/pixel, showing that H 2 O is mostly emanating from the neck connecting the two principal lobes, while CO 2 emanates mostly from both the so-called head and southern latitude regions of the large lobe (Migliorini et al 2016). Moreover, VIRTIS-M has observed the diurnal cycle of the water ice in the neck regions, occurring in the form of transient deposits formed in the upper layer of the surface by recondensation of water molecules sublimated from the subsurface ice (De Sanctis et al 2015).…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations